Status and Potential of Farm Mechanization in North Western Himalayan State Uttarakhand of India - Singh, S.; Singh, R. Kr. (Indian Journal of Hill Farming, 2018)
Uttarakhand is a small hill state situated in North Western Himalayas of India blessed with naturally occurring micro agro-climatic regions suitable for cultivation of a wide range of agri-horticultural crops with a great potential for development. Net sown area of the state is only about 13% of its total reported area. The level of farm mechanization in the state is very poor with respect to mechanical power, efficient implements, water management, renewable energy and post harvest technology sectors. The undulating topography, small and irregular sized fields, lack of skilled manpower, poor facilities of repair & maintenance, poor purchasing power of farmers and non-availability of improved farm implements and machine are some of the main reason for low level of mechanization in the hilly region of the state. Immediate attention of the state government and other funding agencies is required to strengthen the agricultural engineering wing in hills of Uttarakhand to handle the farm mechanization problems. Despite various constraints, there is a vast scope for increasing productivity of land and farmer’s economy through creation of small water resources for irrigation, land development, use of efficient gender friendly farm power and implements, rain water harvest, disseminating renewable energy gadgets and introducing small scale agro based industries employing post harvest engineering principles.